2020
DOI: 10.1002/jcp.29716
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits Müller cell activation and pro‐inflammatory cytokine production via upregulating the MEG3/miR‐204/Sirt1 axis in experimental diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is the most common ocular complication caused by diabetes mellitus and is the main cause of visual impairment in working‐age people. Reactive gliosis and pro‐inflammatory cytokine production by Müller cells contribute to the progression of DR. Melatonin is a strong anti‐inflammatory hormone, mediating the cytoprotective effect of a variety of retinal cells against hyperglycemia. In this study, melatonin inhibited the gliosis activation and inflammatory cytokine production of Müller ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 43 publications
(69 reference statements)
0
29
0
Order By: Relevance
“…In normal conditions, only retinal astrocytes express glial fibrillary acidic protein (GFAP); however, in DR, there is upregulation of this intermediate filament protein in Müller cells, which can be used as a marker of reactive gliosis in the retina [95]. Moreover, activated Müller cells secrete various inflammatory cytokines resulting from the overexpression of innate immunerelated pathways [96,97]. Müller cell studies using diabetic animal models have proposed a potential important role of these cells in retinal water imbalance and vascular abnormalities [58,98].…”
Section: Reactive Gliosis In Drmentioning
confidence: 99%
“…In normal conditions, only retinal astrocytes express glial fibrillary acidic protein (GFAP); however, in DR, there is upregulation of this intermediate filament protein in Müller cells, which can be used as a marker of reactive gliosis in the retina [95]. Moreover, activated Müller cells secrete various inflammatory cytokines resulting from the overexpression of innate immunerelated pathways [96,97]. Müller cell studies using diabetic animal models have proposed a potential important role of these cells in retinal water imbalance and vascular abnormalities [58,98].…”
Section: Reactive Gliosis In Drmentioning
confidence: 99%
“…These findings suggest that the miR-23b-3p/SIRT1/NF-κB feedback loop may exert a crucial role in the establishment and maintenance of metabolic memory in DR ( 87 ). In addition, inhibition of miR-211, miR-29b-3p, miR-221, miR-34a, miR-217, miR-195, miR-377, miR-543, and miR-204 was also reported to upregulate the expression of SIRT1 and improve DR by alleviating apoptosis, inflammation, oxidative stress, angiogenesis, and ER stress ( 88 97 ).…”
Section: The Role Of Sirt1 In Microvascular Complicationsmentioning
confidence: 99%
“…Another SIRT1 agonist, N-acetyl-5-methoxytryptamine, commonly known as melatonin, has been revealed to exert its protective properties in DCM through the prevention of Drp1-mediated mitochondrial fission by SIRT1/PGC1-α pathway ( 37 ). Another study showed that melatonin could also inhibit pro-inflammatory cytokine production in the progression of DR ( 97 ). Recently, Xue et al.…”
Section: Sirt1 As a Potential Drug Target For The Treatment Of Diabetmentioning
confidence: 99%
“…qRT-PCR was conducted with the powerUP SYBR Green Master Mix (Thermo Fisher Scienti c, USA). qRT-PCR was also performed [10]. The primers used in this study is showed in the Supplemental table 1.…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…The western blot analysis was conducted [10]. In brief, the cultured Müller cells and the mice retina were collected and lysed with protein lysate.…”
Section: Western Blotmentioning
confidence: 99%